The role of selected nutrients in supporting pharmacological treatment of Alzheimer's disease - Bracha, Marietta; Jaroch, Alina (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2022)
Alzheimer's disease (AD) is originally a degenerative brain disease with an unexplained etiology and complex pathophysiological processes. It is the most common type of dementia among the elderly, which progresses over the years and causes severe cognitive deficits. The neuropathological features of AD are the occurrence of neurofibrillary degeneration and extracellular amyloid deposits in the form of amyloid plaques. In addition to widely described cognitive disorders or neuropsychiatric symptoms, dementia in Alzheimer's disease leads to progressive wasting of the body. Malnutrition affects up to 25% of patients with dementia syndrome. Studies have shown that diet is an important factor in preventing cognitive decline. Some nutrients such as vitamins B6, B12, C, A, E, folic acid, DHA and EPA, choline, selenium, phospholipids, quercetin, S-allylcysteine may play an important role in improving cognitive functions, slow down neurodegenerative processes in the brain, and support pharmacological methods of treatment of patients diagnosed with Alzheimer's disease.